Holy rhetoric: Anselm's prayers and the phenomenology of divine compassion. Issue 5 (19th October 2020) - Sweeney, Terence
ABSTRACT: In this essay, I examine Anselm's 'Prayers and Meditations' as rhetorical prayers. I consider the basic structure of prayer as address to the Divine. For Anselm, this address is rhetorically structured towards persuading God to reveal himself by the three Aristotelian means of persuasion: character, affect, and argument. Compassion is the phenomenological showing of God as the transcending Good as summoned by the orator. In rhetorical prayer, we take up our existential situation as moved by God to move God. Compassion is the showing-up of God in prayer as revelation of self and Other.